Quality of life and education in time of pandemic, a reflection from the Human Movement Sciences - Penabad-Camacho, María Amalia (2020)
In the educational context, the Universidad Nacional determined procedures to face social confinement by COVID-19. This represented a new lifestyle for the university community and affected their health and quality of life. From the human movement standpoint, the following editorial calls for atention and offers recommendations to build actions in order to counteract the negative effects of the pandemic and take advantage of emerging oportunities.